Association, Haplotype, and Gene-Gene Interactions of the HPA Axis Genes with Suicidal Behaviour in Affective Disorders. (27th November 2013) - Leszczyńska-Rodziewicz, Anna; Szczepankiewicz, Aleksandra; Pawlak, Joanna; Dmitrzak-Weglarz, Monika; Hauser, Joanna
Abstract : Family twin and adoption studies have noted the heritability of specific biological factors that influence suicidal behaviour. Exposure to stress is one of the factors that strongly contribute to suicide attempts. The biological response to stress involves the hypothalamic-pituitary-adrenal axis (HPA). Therefore, we found it interesting to study polymorphisms of genes involved in the HPA axis ( CRHR1, NR3C1, and AVPBR1 ). The study was performed on 597 patients, 225 of whom had a history of suicide attempts. We did not observe any significant differences in the studied polymorphisms between the group of patients with a history of suicide attempts and the control subjects. Our haplotype analysis of the AVPR1b gene revealed an association between the GCA haplotype and suicide attempts; however, this association was not significant after correcting for multiple testing. We did not observe any other association in haplotype and MDR analysis. We report here a comprehensive analysis of the HPA axis genes and a lack of association for genetic variations regarding the risk of suicide attempts in affective disorder patients. Nonetheless, the inconsistencies with the previously published results indicate the importance of the further investigation of these polymorphisms with respect to the risk of suicide attempts.